A STUDY ON THE TEXT READABILITY OF AN ENGLISH TEXTBOOK ENTITLED BRIGHT: AN ENGLISH COURSE FOR JUNIOR HIGH SCHOOL STUDENTS GRADE IX PUBLISHED BY ERLANGGA - M. Dhani Suheri; Fadly Azhar; Afrianto Afrianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted to find and measure the readability level of a textbook Bright: an English Course for Junior High School Students Grade IX. There is no sample and population in this research because almost of reading texts in the textbook are used as the research subject. The way to collect data in this study was by determine an English textbook of Junior High School, identify the text of reading texts on the textbook, read the text, and count the number of sentences, words and syllables of each text. The data were analyzed using Flesch Readability Formula. After analyzing the data of reading texts on the textbook by using Flesch Reading Ease, the result showed that from 13 reading texts, they are categorized into five levels; Easy (1 text), Fairly Easy (4 texts), Standard (4 texts), Fairly Difficult (3 texts), and Difficult (1 text). In average, the texts are in Standard Level. It means that according to the theory of Flesch Reading Formula (reading is formula) by Rudolf Flesch, the texts are in the appropriate level for grade IX students.Keywords: Readability, Textbook